Activity of Anti-plasmodial and Cytotoxicity of Kapur Leaves (Harmsiopanax aculeatus, Harms) Potential Fraction (FG2, FG3 and FG4) Traditionally Used to Treat Malaria in Maluku Indonesia - Rachel Turalely; Mustofa Mustofa; Mahardika Agus Wijayanti; Triana Hertiani (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2018)
Harmsiopanax aculeatus, Harms, also known as kapur, have been traditionally used as medicinal plants to treat malaria in Maluku, Indonesia, although scientific evidence of the antimalarial active compounds of this plant has not been studied. This study was conducted to evaluate the anti-plasmodial and cytotoxicity activity of the active fraction of H. aculeatus leaves. The fractions tested were FG2, FG3 and FG4 obtained by separation of methanol extract using Vacuum Liquid Chromatography (VLC) by gradually using n-hexane, chloroform, ethyl acetate and methanol solvents. Anti-plasmodial activity in vitro was evaluated in Plasmodium falciparum strain FCR3 which is chloroquine resistant using microscopic method. The activity of cytotoxicity against vero cells was evaluated using MTT colorimetric method. The anti-plasmodial activity and cytotoxicity were expressed by IC50, inhibitory concentration of 50% Plasmodium or cells growth after incubation with the fraction tested, which calculated using probit regression analysis with SPSS.  The results showed that the fraction of FG2, FG3 and FG4 had a promising anti-plasmodial activity with IC50 value of 7.48; 8.24 and 7.75 μg/mL, respectively. The cytotoxicity activity of the three fractions on vero cell were 5814.43; 7780.48 and 1022.44 μg/mL, respectively. Moreover, the selectivity index (IC50 Vero cells/IC50 Plasmodium) of those were 777.33,944.23 and 131.93, respectively indicated that the three fractions were active, non-toxic and selective against P. falciparum. Further study will be conducted to isolate the active compounds of the fraction.